MENYUSURI JEJAK DAKWAH: EVOLUSI MITRA DAKWAH HABIB HUSEIN JA’FAR DALAM ERA DIGITAL - Farhan Ansharullah Ahmad; Mustafa Kharis Syaiful Yahya; Ali Nurdin; Najmy Hanifah (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2024)
This research explores the evolution of da'wah partners in the context of contemporary da'wah practiced by Habib Husein Ja'far. Using a qualitative approach, this study conducted in-depth interviews, case studies, social media content analysis, document analysis, and participatory observation to understand da'wah strategies, the typology of da'wah partners, and the dynamics of digital da'wah. The results illustrate that Habib Husein Ja'far's da'wah reflects an evolution in methods, strategies, and typology of da'wah partners. The contemporary approaches used, including the use of social media and technology, contribute significantly to the dissemination of Islamic religious messages. The conclusion of this research provides in-depth insight into the adaptation of da'wah to social and cultural dynamics, and provides new insights into da'wah in the digital era.